UPAYA GURU PENDIDIKAN AGAMA ISLAM MENGATASI KESULITAN BELAJAR SISWA BIDANG STUDI PENDIDIKAN AGAMA ISLAM DI KELAS VIII C SMP NEGERI 1 SEMPARUK TAHUN PELAJARAN 2022/2023 - Abdul Wahid; Arnadi, Parni (ADISAM PUBLISHER, 2026)
Learning difficulties are the core of educational problems, because learning is the main activity in education. All efforts in education and teaching are directed so that students learn, because through these learning activities students can develop more optimally. The approach and type of research used in this research is a qualitative approach using phenomenological research. Based on the results of observations conducted by researchers at SMP Negeri 1 Semparuk, it was found that there were several students who experienced learning difficulties in Islamic Religious Education subjects, which included the classroom atmosphere being not conducive, students' understanding of the material, understanding of students' moral behavior according to the material, and students' habituation according to the material is still very lacking. The efforts made by PAI teachers to overcome students' learning difficulties are as follows: a) Creating a conducive classroom atmosphere b) Approaching students c) Providing Motivation, Guidance and Direction d) Reviewing or repeating material e) Providing exercises or assignments and f) Using varied methods.